The echo in flu-vaccination echo chambers: Selective attention trumps social influence. Issue 8 (18th February 2020) - Giese, Helge; Neth, Hansjörg; Moussaïd, Mehdi; Betsch, Cornelia; Gaissmaier, Wolfgang
Highlights: This study scrutinizes how vaccination arguments propagate in chains of people. Shared arguments depend on prior attitudes independently of the received arguments. Homogenous groups are not more extreme in their arguments than heterogenous ones. Abstract: Background: Online discussions may impact the willingness to get vaccinated. This experiment tests how groups of individuals with consistent and inconsistent attitudes towards flu vaccination attend to and convey information online, and how they alter their corresponding risk perceptions. Methods: Out of 1859 MTurkers, we pre-selected 208 people with negative and 221 people with positive attitudes towards flu vaccinations into homogeneous or heterogeneous 3-link experimental diffusion chains. We assessed (i) which information about flu vaccinations participants conveyed to the subsequent link, (ii) how flu-vaccination related perceptions were altered by incoming messages, and (iii) how participants perceived incoming information. Results: Participants (i) selectively conveyed attitude-consistent information, but exhibited no overall anti-vaccination bias, (ii) were reluctant to alter their flu-vaccination related perceptions in response to messages, and (iii) evaluated incoming information consistent with their prior attitudes as more convincing. Discussion: Flu-vaccination related perceptions are resilient against contradictions and bias online communication. Contrary to expectations, there was no sign of amplification of anti-vaccine attitudes by online communication.